PENERAPAN SISTEM PERENCANAAN KEBUTUHAN KOMPONEN UNTUK MEMENUHI KEBUTUHAN HUB TIPE SUPRA PADA PT ASTRA HONDA MOTOR - Arifin, Yusuf; Fadlillah, Siti Nur (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
Planning system of customer needs in Astra Honda Motor Company using Material Requirement Planning system with order applying several metods, for example Lot for Lot, POQ, and EOQ. The disadvantages of those applied system is not knowing which method is the most advantages. Therefore, a research on how to compare the having cost for each method is needed. The result, Lot For Lot (LFL) method is the methodÂ minimal cost.